Low spatial mobility of associated microbes along the hyphae limits organic nitrogen utilization in the arbuscular mycorrhizal hyphosphere - Vieira, Caroline Krug; Rozmoš, Martin; Kotianová, Michala; Hršelová, Hana; Bukovská, Petra; Jansa, Jan (Frontiers in Plant Science, 2026)
BacgroundArbuscular mycorrhizal (AM) fungi enhance plant nutrient acquisition from soil; however, their ability to exploit organic nutrient forms in the absence of associated microbes capable of mineralization remains unclear.MethodsTo test if the AM fungi carry their beneficial bacterial partners into nutrient-rich zones, we conducted three controlled experiments manipulating the microbial inputs, diversity and composition in plant–AM fungus–soil systems, ranging from open pots to semi-sterile mesocosms. We manipulated soil microbial diversity by imposing a microbial diversity gradient (complex communities fractionated by size, resulting in fractions passing through 1 µm to 1000 µm sieves) and cultivated Andropogon gerardii in previously sterilized substrate together with a bacterial-free Rhizophagus irregularis. In each experiment, 15N‐labeled chitin or mineral nitrogen (N) compartments were installed in the root‐free zone of each mesocosm.ResultsWith decreasing microbial inputs into the root-free zone, the N uptake from chitin to plants, facilitated by the AM fungal hyphae, decreased. Upon complete absence of microbes in the root-free zone, AM hyphal foraging preferences assessed by quantitative PCR indicated that exploration of the mineral N compartments was more effective than that of the chitin compartments. The AM fungal hyphae were ineffective in priming mineralization of organic N even if provided with complex soil microbiomes at a distance from the compartment.ConclusionsIn summary, chitin-enriched compartments become attractive for the AM fungi only when previously mineralized by competent microbes. Such microbes, however, were not effectively transported to spatially restricted organic resources in soil via AM hyphal highways in our experiments.